Recuperação de águas residuárias geradas na indústria de produtos lácteos por sistema híbrido para fins de reúso - Schmitt, Dalila Maria Formentini (2018)
The whey industrialization process generates effluents that need a special attention regarding treatment and final disposal. Currently, many advanced treatment techniques have been studied in order to provide a treated water with high quality for reuse purposes. In this context, this work aimed at evaluating the efficiency of a hybrid system based on coagulation/flocculation/sedimentation (C/F/S) and nanofiltration (NF) for industrial reuse purposes. In the C/F/S process, the use of Moringa oleifera Lam (Moringa) seeds as a natural coagulant was evaluated. Different methods and saline solutions (KCl, MgCl2.6H2O, and CaCl2.2H2O) were studied when extracting the active components from the seeds. Nanofiltration was performed with polyamide membranes based on the tangential flow filtration principle. The extraction method that utilized the whole Moringa, ground directly with the saline solution, was highlighted among the evaluated ones, by using a smaller number of steps. The extraction with calcium chloride dehydrated demonstrated the best efficiency, compared to the magnesium chloride hexahydrate and potassium chloride. The C/F/S step was optimized through serial factorial designs, in which the turbidity removal was the response variable. It was obtained a turbidity removal of 91.52% when using 300 mg L-1 of the Moringa coagulant (MC), extracted with a saline CaCl2.2H2O solution (0.9 mol L-1) and a pH value of 10.0. The empirical quadratic model obtained, validated by the ANOVA and F-test, in conjunction with the desirability function, demonstrated the possibility to obtain turbidity removals of 92.04 % ( 9.13%) with the following conditions: MC = 300 mg L-1, CCaCl2 = 0.9 mol L-1 e pH = 11.0. The sedimentation time was reduced from 40 to 25 minutes. The MC performance concerning the turbidity removal proved to be dependent on the alkaline pH (8.0 to 11.0). In the nanofiltration process, it was evaluated the influence of the C/F/S optimized as a pre-treatment, comparing the hybrid C/F/S/NF and the direct NF at 4 bar. High removals of apparent color (99.7%), turbidity (99.1%), COD (88.9%), total hardness (66.3%), and calcium (63.7%) were obtained using the hybrid treatment system, providing a removal of 81.2% in the membrane fouling, compared to the raw NF treatment. The proposed hybrid system allows the reuse of this wastewater in the industry.